Anthropogenic Sources of Non-Migratory Avian Mortalities In Singapore - David J. X. TAN; Ding Li YONG; Bing Wen LOW; Alan OWYONG; Alfred CHIA (The International Journal of Tropical Veterinary and Biomedical Research, 2017)
Although urban spaces are increasingly recognised as viable habitats for wildlife, cities remain a major source of anthropogenic mortality for wild birds. While the sources of urban avian mortalities have been well documented in North America, these phenomena remain poorly studied in Southeast Asia, especially for resident species. Here we present the first summary of non-migratory urban bird mortalities for the heavily urbanised island of Singapore. We conducted a citizen science study using print and social media outreach to encourage members of the public to report their observations of dead birds between November 2013 and October 2017, and collected a total of 362 mortality records across 65 resident bird species and five mortality sources. Our results show that a diverse array of bird species is directly impacted by anthropogenic sources of mortality, although mortalities stemming from roadkill and cat predation are likely to be undersampled. We also find that forest-edge frugivores such as the Pink-necked Green Pigeon are likely to be especially vulnerable to building collisions. Our study shows that despite its limitations, opportunistic sampling using citizen science can generate large amounts of ecological data at relatively low cost, and serve as a cost-effective complement to standardised survey methodologies.